Physiological and exploitation aspects of Acacia mangium Willd. A review (2018)
Acacia mangium is a fast-growing legume species native to Australia and Central Asia, whose use has spread throughout the world because of its short rotation cycle, morphology, wood workability and high adaptability to different climatic and soil conditions. Additionally, it has a potential for use in crop by-products, as well as for recovery of degraded soils. From the morpho-physiological point of view, one important feature is the presence of phyllodes, widened petioles formed after four weeks of age, when the true leaves are lost, which perform photosynthetic activity and confer plant tolerance to dry environments for prolonged periods of time. The symbiotic association with nitrogen-fixing bacteria and mycorrhizal fungi facilitates nutrient uptake in low-fertility soils. Acacia mangium flowering is induced by genes that may be related to temperature, photoperiod and signaling activation by sucrose, but can occur at any time of year. Flowering peaks are recorded according to the species location. Although this species has been cultivated in Colombia for many years, many aspects of its response to different cultivation conditions and the quality of introduced genetic materials are still unknown.